Performance indicators for hospital nursing service: integrated review - Graziela Caldana; Carmen Silvia Gabriel; Andréa Bernardes; Yolanda Dora Martinez Évora (Rev Rene)
An effective way of assessing the performance of nursing services and their management is through the use of indicators that show its evolution over time, allowing comparison with internal and external benchmarks. This study aimed at highlighting and examining through an integrated review, indicators that evaluate the quality of nursing care in hospital settings. For data collection, the following database was used: MEDLINE, LILACS, CINAHL, COCHRANE and BDENF. The sample of this study consisted of 15 articles published between 1998 and 2009. After analyzing the articles included in the review, the results of the studies were classified according to the triad proposed by Donabedian: Indicators of processes, structure and results. The articles which have been examined have a wide range of indicators which can support nurses in assessing the quality of nursing care in hospitals.